Infant cry classification to identify asphyxia using time-frequency analysis and radial basis neural networks - Muthusamy, Hariharan; Jeyaraman, Saraswathy; Sindhu, Ravindran; Wan Khairunizam, Wan Ahmad, Dr.; Sazali, Yaacob, Prof. Dr. (Elsevier Ltd, 2013)
Link to publisher's homepage at http://www.elsevier.com/